2015
DOI: 10.1002/ppul.23325
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary ventilation and micro‐structural findings in congenital diaphragmatic hernia

Abstract: Functional and micro-structural changes persist into adulthood in most CDH patients. Ipsilateral elevated (3) He ADC values are consistent with enlargement of mean dimensions of the confining lung micro-structure at the alveolar level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
1
27
0
Order By: Relevance
“…In a cohort born before ECMO was introduced in the Netherlands (1991), mild airflow obstruction had deteriorated from childhood to young adulthood . Microstructural pulmonary changes not only in the ipsilateral lung but also in the contralateral lung were found in nonsmoking young adults in this cohort . Taking into account the very short duration of mechanical ventilation in this older group and the change in mortality rates over time, we assume that children with CDH who survived in the past decade suffered from more severe lung hypoplasia, were ventilated longer, and have more airflow obstruction.…”
Section: Discussionmentioning
confidence: 94%
“…In a cohort born before ECMO was introduced in the Netherlands (1991), mild airflow obstruction had deteriorated from childhood to young adulthood . Microstructural pulmonary changes not only in the ipsilateral lung but also in the contralateral lung were found in nonsmoking young adults in this cohort . Taking into account the very short duration of mechanical ventilation in this older group and the change in mortality rates over time, we assume that children with CDH who survived in the past decade suffered from more severe lung hypoplasia, were ventilated longer, and have more airflow obstruction.…”
Section: Discussionmentioning
confidence: 94%
“…In previous studies, we showed that children born with major anatomical foregut anomalies and/or treated with ECMO are at risk for long‐term respiratory morbidity, reduced exercise capacity, and even deterioration of exercise capacity . In this RCT, we aimed to evaluate whether these children's exercise capacity can be improved.…”
Section: Perspectivementioning
confidence: 99%
“…We previously showed that children with CDH and EA are at risk for long‐term persistent respiratory morbidity, reduced exercise capacity, and motor function problems . Moreover, exercise capacity in neonatal ECMO survivors deteriorated between 5 and 12 years of age .…”
Section: Introductionmentioning
confidence: 99%
“…Since the respiratory system cellular maintenance and repair systems rely on a sufficiently numerous and well‐positioned set of progenitor cells, it would be expected that disruption of this repertoire would have long term effects on the respiratory system development. For example, Spoel et al imaged adult congenital diaphragmatic hernia survivors using hyper‐polarized 3 H‐MRI and demonstrated persistent micro‐structural alveolar enlargement.…”
Section: Neonatologymentioning
confidence: 99%